Does Board Diversity Influence Green Revenue and Firm Value? Evidence From an Emerging Market - Laila Mohamed Alshawadfy Aladwey (Emerging Science Journal, 2026)
This study investigates the effect of board diversity on green revenue among Saudi-listed firms. It places particular emphasis on the moderating role of shareholder value. To achieve this objective, the study constructs a composite board diversity index using principal component analysis (PCA). It employs random-effects panel regression models on firm-level data covering the period 2020–2024. Robustness is ensured through alternative model specifications and Generalized Method of Moments (GMM) estimations. The findings reveal that board diversity is positively associated with green revenue. In contrast, higher shareholder value, as measured by market valuation, is negatively associated with green revenue. Importantly, board diversity significantly mitigates this negative relationship. This indicates that diverse boards encourage stronger engagement in sustainable activities, even in highly valued firms. The study contributes to the literature by integrating board diversity, green revenue, and shareholder value within a single empirical framework in an emerging market context. The results offer novel evidence that board diversity serves as an effective governance mechanism for aligning sustainability objectives with value-driven corporate strategies. From both theoretical and policy perspectives, the findings support agency and resource-dependence theories. They highlight the importance of inclusive board structures in embedding sustainability into corporate decision-making.